Panorama do mercado farmacêutico veterinário: desafios e perspectivas - Nakaira, Lilian Saemi Arita (Universidade Estadual Paulista (Unesp), 2022)
With the exponential growth of this sector in Brazil and in the world, national companies felt the need to restructure their processes in search of cost reduction and productivity optimization. Therefore, the practice of outsourcing has become increasingly frequent due to its advantages. However, this alternative poses risks in terms of product quality. In addition, national companies face difficulties in carrying out Research and Development, as they lack qualified alternatives. In this way, the supervision processes of the quality assurance system and monitoring of veterinary clinical studies carried out by MAPA, need urgent restructuring. It is observed that the expansion of this market is also accompanied by numerous challenges that, together with the emergence of the Covid-19 pandemic, gave rise to many uncertainties regarding the offers and growth strategies for this sector in Brazil. To develop this content, technical-scientific articles, technical reports from legal associations and the National Legislation, which were relevant to the chosen theme, were consulted. It was selected 29 texts of 48 previously found to obtain data. Based on this analysis, it was possible to conclude that, despite the difficulties of the pandemic, the veterinary pharmaceutical market did not suffer economic losses, thanks to the search for greater care with a health animal, both in the pet segment and in the production animal segment, due to new scenario circumstances, which led to changes in consumer habits

Com o crescimento exponencial deste setor no Brasil e no mundo, as empresas nacionais sentiram a necessidade de reestruturar seus processos em busca da redução de custos e otimização da produtividade. Dessa forma, a prática terceirização tem se tornado cada vez mais frequente devido a suas inúmeras vantagens. Contudo, essa alternativa oferece riscos quanto à qualidade do produto. Além disso, as empresas nacionais enfrentam dificuldades para a realização de Pesquisa e Desenvolvimento, pois carecem de alternativas qualificadas. Dessa forma, os processos de inspeção do sistema de garantia de qualidade e o acompanhamento dos estudos clínicos veterinários exercidos pelo MAPA, necessitam de urgente reestruturação. Observa-se que a expansão desse mercado também é acompanhada por inúmeros desafios que, unidos ao surgimento da pandemia de Covid-19, gerou muitas incertezas quanto às previsões e estratégias de crescimento para esse setor no Brasil. Para a elaboração do conteúdo, foram consultados artigos técnicos-científicos, relatórios técnicos de organizações legais e a Legislação Nacional, de relevância para o tema abordado. Foram selecionados 29 textos de 48 previamente listados para obtenção dos dados. Com base nesta análise, foi possível concluir que, apesar das dificuldades da pandemia, o mercado farmacêutico veterinário não sofreu prejuízos econômicos, graças à busca por maiores cuidados com a saúde animal, tanto no segmento pet, como no segmento de animais de produção, devido às circunstâncias deste novo cenário, que levou a mudanças de hábitos dos consumidores.
Veterinary pharmaceutical market overview: challenges and prospects
Keywords: Veterinary pharmaceutical market; Veterinary industry; Animal health; Mercado farmacêutico veterinário; Indústria veterinária; Saúde animal